2013
DOI: 10.1186/1479-5876-11-167
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral localization and activity of 17β-hydroxysteroid dehydrogenase type 1 in non-small cell lung cancer: a potent prognostic factor

Abstract: BackgroundEstrogens were recently demonstrated to be synthesized in non-small cell lung carcinomas (NSCLCs) via aromatase activity and aromatase inhibitor (AI) did suppressed estrogen receptor (ER) positive NSCLC growth. However, other enzymes involved in intratumoral production and metabolism of estrogens, i.e. 17β-hydroxysteroid dehydrogenases (i.e. 17βHSD1 and 17βHSD2) and others have not been studied. Therefore, in this study, we examined the clinical/ biological significance of 17β-hydroxysteroid dehydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 27 publications
5
24
0
Order By: Relevance
“…However, no association between the intratumoral E2 concentration and the expression of HSD17B1 was found in mentioned study. Nonetheless, Verma et al have recently examined the significance of HSD17B1 enzyme in NSCLC using immunohistochemical staining of patients' tissue sections [50]. A higher HSD17B1 immunoreactivity in investigated cancerous specimens was positively correlated with the presence of CYP19A1, tumor stage and with a high intratumoral E2/E1 ratio.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, no association between the intratumoral E2 concentration and the expression of HSD17B1 was found in mentioned study. Nonetheless, Verma et al have recently examined the significance of HSD17B1 enzyme in NSCLC using immunohistochemical staining of patients' tissue sections [50]. A higher HSD17B1 immunoreactivity in investigated cancerous specimens was positively correlated with the presence of CYP19A1, tumor stage and with a high intratumoral E2/E1 ratio.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, results of retrospective analyses revealed that postmenopausal women diagnosed with NSCLC had significantly better survival rates than premenopausal women and men [57]. High levels of E2 detected in serum were connected with poorer clinical outcome for NSCLC male patients and increased intratumoral level of HSD17B1 was associated with their worse overall survival [17,50].…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation of HSD17B1 in response to E2 stimulation is relatively rapid, occurring after 24 hours and becoming more prominent after prolonged exposure. In breast cancer patients, E2 depletion was accompanied by an increase in HSD17B1 expression (90), and similar observations were made in lung cancer (91). In regard to HSD17B2, there appears to be a timesensitive response in response to E2.…”
Section: Discussionsupporting
confidence: 63%
“…It was hypothesized that this upregulation of HSD17B1 could be a response to estrogen depletion where the tissue attempts to restore estrogen signaling by alternative pathways (90). Supporting findings were made using lung cancer cell lines A549 and LK87, in which aromatase inhibitor treatment resulted in increased HSD17B1 expression (91). In ERα-and AR-positive breast cancer cell line T-47D, aromatase inhibitor treatment resulted in increased HSD17B2 and DHT expression.…”
Section: Control Of Expression and Regulation Of Hsd17b1 And Hsd17b2supporting
confidence: 52%
“…Coincidentally, estrogen receptors are also reported to play a key role in the progression of various types of NSCLC including adenocarcinoma (ADCA), SCLC, and large-cell carcinoma [10]. Moreover, the clinical and biological significances of estrogen metabolisms has been studied in NSCLCs and they might play critical roles in regulating lung cancer biology [11]. However, effects of E2 on the progression of NSCLC, especially for SCLC, have not been adequately studied and whether E2 could be a candidate treatment for SCLC was rarely studied.…”
mentioning
confidence: 99%